ChemInform Abstract: New Route to the 5‐((Arylthio‐ and Heteroarylthio)methylene)‐3‐(2, 2, 2‐trifluoroethyl)‐furan‐2(5H)‐ones (II) —Key Intermediates in the Synthesis of 4‐Aminoquinoline γ‐Lactams (IV) as Potent Antimalarial Compounds. Issue 13 (1st April 2014) - Kanishchev, Oleksandr S.; Lavoignat, Adeline; Picot, Stephane; Medebielle, Maurice; Bouillon, Jean‐Philippe
Abstract Most new compounds (IV) exhibit good in vitro activity against P.